Energy-efficient substrate pasteurisation for combined production of shiitake mushroom (Lentinula edodes) and bioethanol. (February 2019) - Xiong, Shaojun; Martín, Carlos; Eilertsen, Lill; Wei, Maogui; Myronycheva, Olena; Larsson, Sylvia H.; Lestander, Torbjörn A.; Atterhem, Lars; Jönsson, Leif J.
Graphical abstract: Highlights: An innovative method of using hot-air for substrate pasteurisation was evaluated. Hot-air pasteurisation was more energy efficient and lower cost than autoclaving. Hot-air pasteurisation resulted in improved mushroom growth and yield. Fungal growth reduced the mass fraction of lignin to less than half of the initial. Both methods resulted in spent substrate with comparable enzymatic convertibility. Abstract: Hot-air (75–100 °C) pasteurisation (HAP) of birch-wood-based substrate was compared to conventional autoclaving (steam at 121 °C) with regard to shiitake growth and yield, chemical composition of heat-pretreated material and spent mushroom substrate (SMS), enzymatic digestibility of glucan in SMS, and theoretical bioethanol yield. Compared to autoclaving, HAP resulted in faster mycelial growth, earlier fructification, and higher or comparable fruit-body yield. The heat pretreatment methods did not differ regarding the fractions of carbohydrate and lignin in pretreated material and SMS, but HAP typically resulted in lower fractions of extractives. Shiitake cultivation, which reduced the mass fraction of lignin to less than half of the initial without having any major impact on the mass fraction of glucan, enhanced enzymatic hydrolysis of glucan about four-fold. The choice of heating method did not affect enzymatic digestibility. Thus, HAP could substitute autoclaving and facilitate combined shiitake mushroom and bioethanol production.